Synthesis of mono and bis-substituted asymmetrical compounds, (1-(pyridin-2-yl)ethylidene)carbonohydrazide and 1-(2’-hydroxybenzylidene)-5-(1’-pyridylethylidene)carbonohydrazone: Structural characterization and antioxidant activity study - Seck, Thierno Moussa; Faye, Fatou Dieng; Gaye, Aissatou Alioune; Thiam, Ibrahima Elhadji; Diouf, Ousmane; Gaye, Mohamed; Retailleau, Pascal (European Journal of Chemistry, 2020)
Carbonohydrazide was used for synthetizing a new dissymmetrical bis-substituted Schiff base 1-(2’-hydroxybenzylidene)-5-(1’-pyridylethylidene)carbonohydrazone (2). A mono substituted compound (1-(pyridin-2-yl)ethylidene)carbonohydrazide (1) was firstly prepared by condensation reaction of carbonohydrazide and 2-acetylpyridine in 1:1 ratio. Secondly, compound 2 was obtained by condensation reaction of compound 1 and salicylaldehyde in 1:1 ratio. The prepared compounds were characterized by elemental analysis, infrared and 1H and 13C NMR spectroscopy techniques, and the structure of compound 2 was determined by single-crystal X-ray diffraction study. The compound 2 (C15H15N5O2) crystallises in the monoclinic space group P21/c with the following unit cell parameters: a = 8.3683(3) Å, b = 13.9986(4) Å, c = 12.1610(4) Å, β = 97.512(3)°, V = 1412.37(8) Å3, Z = 4, T = 100(2) K, μ(MoKα) = 0.098 mm-1, Dcalc = 1.398 g/cm3, 6057 reflections measured (5.708° ≤ 2Θ ≤ 54.962°), 6057 unique (Rsigma = 0.0395) which were used in all calculations. The final R1 was 0.0474 (I > 2σ(I)) and wR2 was 0.1971 (all data). The oxygen atom O1 and the azomethine nitrogen atom N5 adopt cis-configuration relative to the C8-N4 bond, while O1 adopts trans-configuration with the azomethine nitrogen atom N2 relative to C8-N3 bond. The crystal packing of compound 2 is stabilized by intramolecular O(phenol)–H···N(carbohydrazide) and intermolecular N (carbohydrazide)–H···O (carbo-hydrazide) hydrogen bonds which form layers parallel to [010] axis. Additional C–H···O hydrogen bond consolidate the structure. The carbonohydrazide moiety C=N–N–C(O)–N–N=C fragment and the phenyl ring are almost coplanar; with an angle of 1.73(1)° between their means plans. The dihedral angle between the mean planes of the phenyl and the pyridine rings is 22.267(2)°.